ACTIVITY OF ALANIN AMINOTRANSFERASE AND ASPARTATE AMINOTRANSFERASE OF BALI CATTLE INFECTED BY FASCIOLA GIGANTICA - Dharmayudha, Anak Agung Gde Oka; Kusumadarma, Ida Bagus Dimas; Ardana, Ida Bagus Komang; Anthara, Made Suma; Gunawan, I Wayan Nico Fajar; Sudimartini, Luh Made; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 10 No. 1 Pebruari 2018DO - 10.24843/bulvet.2018.v10.i01.p14, 2018)
Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) are aminotransferase group enzymes which often used as parameters of liver damage. The purpose of this study is to determine the effect of Fasciola gigantica infections in bali cattle on the activity of ALT and AST. The materials used were 60 bali cattle blood samples consisting of 30 samples of blood were infected Fasciola gigantica and 30 blood samples were not infected with Fasciola gigantica . Blood samples were taken at the time of the slaughter placed in non EDTA tube. Data were analyzed using Independent Samples T-Test . The results showed a mean ALT levels in the blood of infected Bali cattle Fasciola gigantica was 78.73 U/L. It was not significant on the increase in ALT levels compared with uninfected bali cattle Fasciola gigantica 57.23 U/L, While the average AST levels in the bali cattle blood which were infected by Fasciola gigantica was 108.43 U/L. It was highly significant increased AST compared with non-infected Bali cattle Fasciola gigantica 78.13 U/L.